State of play: Live original music venues in Western Australia - Bennett, Dawn (Department of Contemporary Music Studies, 2010)
Just as music is fundamental to the vibrancy of cities and regions, venues are central to music. With a focus on live original music, this project gave a voice to venues across Western Australia, gathering data relating to capacity, audiences, performance activity and genre. Significant barriers to hosting live original music were revealed as overly complex licensing and legislative processes, the gentrification of key entertainment areas and changing musical tastes. Combined, these barriers have resulted in a decline in the number of small to medium-sized venues hosting live original music. Findings, common to many locations, suggest the need for urgent action to develop new audiences, enhance performance opportunities, overcome a dominant 'cover band' culture and assist venue managers to find their way through the legislative maze.